Determinants of green marketing mix in developing economies: Conceptualisation and scale validation approach. Issue 4 (18th May 2020) - Mehraj, Danish; Qureshi, Ishtiaq Hussain
Abstract: Growing environmental issues and rising concerns about sustainable development are rapidly shifting the traditional marketing and forcing organisations to practice green marketing mix. In an attempt to revisit present‐day environmental issues which are related to the industry, this paper provides a glimpse about the nature of green marketing mix in the Indian context. To validate the model, data were collected from 450 firms and was analysed using an appropriate statistical tool. The results identified four factors for green marketing mix scale: (a) Green Solution, (b) Green Information, (c) Green Value and (d) Green Access. The findings contribute to the theory of green marketing concept. The study is expected to provide valuable insights into the green marketing mix for the industry, which can be of immense help to local and global marketers. Further, it provides a wide‐ranging scale for the academic researchers who want to explore the green marketing mix in different organisational settings as a base for future study.